2016
DOI: 10.1515/enr-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

The role of retinoic acid receptors and their cognate ligands in reproduction in a context of triorganotin based endocrine disrupting chemicals

Abstract: Retinoic acid (RA), an active form of vitamin A, regulates the embryonic development, male and female reproduction and induces important effects on the cell development, proliferation, and differentiation. These effects are mediated by the retinoid (RAR) and rexinoid nuclear receptors (RXR), which are considered to be a ligand-activated, DNA-binding, trans-acting, and transcription-modulating proteins, involved in a general molecular mechanism responsible for the transcriptional responses in target genes. Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Due to the induction of progesterone biosynthesis, effects on aromatase activity, and the capability of inducing the transcriptional activity of thyroid hormone receptor, these compounds are endocrine-disrupting agents [ 10 , 11 , 12 ]. Moreover, as retinoid X receptor ligands, these compounds may induce multimodal alterations of the cell phenotype [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the induction of progesterone biosynthesis, effects on aromatase activity, and the capability of inducing the transcriptional activity of thyroid hormone receptor, these compounds are endocrine-disrupting agents [ 10 , 11 , 12 ]. Moreover, as retinoid X receptor ligands, these compounds may induce multimodal alterations of the cell phenotype [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organotin compounds have many biological impacts and are associated with endocrine and physiologic disruptor effects, acting as EDCs ( 50 ). It was recently demonstrated that they are able to bind nuclear receptor, such as glucocorticoid receptors and retinoid X receptor subtypes, forming a complex OTs-nuclear receptors with coactivators and inducing transcription of target genes ( 51 , 52 ). This process promotes changes in the expression of proteins in addition to mitochondrial and cell dysfunctions ( 51 , 52 ).…”
Section: Organotins Challenge Kidneys With Oxidative Stressmentioning
confidence: 99%
“…Binding to these nuclear receptors results in energy metabolism disruption supportive of its obesogenic ability (reviewed in (Veiga-Lopez et al 2018)). TBT can also interfere with reproductive function (reviewed in (Delgado et al 2011;Macejova et al 2016)) and result in early embryonic loss (Harazono and Ema 2000). In aquatic organisms, TBT can act as an estradiol sulfation inhibitor and reduce steroid synthesis and specific metabolism pathways in fish (Thibaut and Porte 2004).…”
Section: Introductionmentioning
confidence: 99%